2006
DOI: 10.1002/eej.20461
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet‐based fast discrimination of transformer magnetizing inrush current

Abstract: Recently customers who have sensitive industrial loads have been installing co-generation facilities. They can avoid voltage sags and other distribution system related disturbances by supplying electricity to important load from their generators. For another example, FRIENDS, highly reliable distribution system using semiconductor switches or storage devices based on power electronics technology, is proposed. These examples illustrate that the need for high reliability in distribution system is increasing. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…It can be seen that unlike the noise‐free signal, spikes have occurred consistently and do not decay to zero rapidly. So, it can be said that wavelet‐based methods such as the methods suggested in [14, 15, 37] can be affected by noise. More details about these methods can be found in [14, 15, 37].…”
Section: Analogy With Wavelet Transform‐based Methodsmentioning
confidence: 99%
“…It can be seen that unlike the noise‐free signal, spikes have occurred consistently and do not decay to zero rapidly. So, it can be said that wavelet‐based methods such as the methods suggested in [14, 15, 37] can be affected by noise. More details about these methods can be found in [14, 15, 37].…”
Section: Analogy With Wavelet Transform‐based Methodsmentioning
confidence: 99%
“…It is found that the noise has an obvious effect on the wavelet transform and it is difficult to distinguish between the internal fault and the inrush current. Hence, the spike-shaped waveforms affect the wavelet-based method (such as in [8], [14], and [32]) in a noisy environment.…”
Section: Comparison Between S-transform and Wavelet Transformmentioning
confidence: 99%
“…hence, a large computational burden is required. Discrete wavelet transform (DWT)-based algorithms for discriminating between the magnetizing inrush current and short circuit current were suggested in [8] and * Correspondence: az.ashrafian@gmail.com [9]. Moreover, protective methods have been proposed using a combination of DWT and fuzzy logic [10,11], neural networks [5,12], Gaussian mixture model [13], correlation factor [14], and support vector machine [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature for fault detection, several decision algorithms 1–42 have been developed to be employed in the protective relay for preventing maloperation of the protective equipment under different nonfault conditions, including magnetizing inrush current, ratio mismatch, through‐fault current, etc. There are many techniques 1–42 for detecting faults, such as artificial neural networks (ANNs) 12,30,39,40, transient‐based protection 13,18–20, finite element 14, fuzzy logic 35, hybrid systems 14,32, and so on. An algorithm for protecting a transformer with three windings using the increments of flux linkages (IFLs) has been proposed by Kang et al 2.…”
Section: Introductionmentioning
confidence: 99%